A hybrid enzymatic zinc-air fuel cell - Abdul Aziz Ahmad,; Raihan Othman,; Faridah Yusof,; Mohd Firdaus Abd Wahab, (Universiti Kebangsaan Malaysia, 2014)
A hybrid biofuel cell, a zinc-air cell employing laccase as the oxygen reduction catalyst is investigated. A simple cell design is employed; a membraneless single chamber and a freely suspended laccase in the buffer electrolyte. The cell is characterised based on its open-circuit voltage, power density profile and galvanostatic discharge at 0.5 mA. The activity of laccase as an oxidoreductase is substantiated from the cell discharge profiles. The use of air electrode in the cell design enhanced the energy output by 14%. The zinc-air biofuel cell registered an open-circuit voltage of 1.2 V and is capable to deliver a maximum power density of 1.1 mWcm-2 at 0.4 V. Despite its simple design features, the power output is comparable to that of biocatalytic cell utilising a much more complex system design.